Use of vonoprazan, a novel potassium-competitive acid blocker, for the treatment of proton pump inhibitor-refractory reflux esophagitis in patients with systemic sclerosis. Issue 1 (February 2022) - Shirai, Yuichiro; Kawami, Noriyuki; Iwakiri, Katsuhiko; Kuwana, Masataka
Objective: Proton pump inhibitor-refractory reflux esophagitis is one of the intractable conditions of systemic sclerosis for which new treatments are required. Vonoprazan is a novel potassium-competitive acid blocker and has been shown to have several advantages over conventional proton pump inhibitors, including a long duration of gastric acid suppression. Methods: To investigate the efficacy of vonoprazan for treating proton pump inhibitor-refractory reflux esophagitis in patients with systemic sclerosis, 10 patients with proton pump inhibitor-refractory reflux esophagitis who were switched to vonoprazan were selected from our systemic sclerosis database. Reflux esophagitis was evaluated by endoscopy, and gastroesophageal reflux disease–related symptoms were assessed by the frequency scale for the symptoms of gastroesophageal reflux disease questionnaire before and after switching from proton pump inhibitor to vonoprazan at an average interval of 3.5 [2–5.5] months. Results: After switching patients to vonoprazan, the endoscopic findings of reflux esophagitis were significantly improved ( p  = .033), and six patients (60%) achieved mucosal healing. The total frequency scale for the symptoms of gastroesophageal reflux disease score was also significantly decreased ( p  = .043), mainly by improving the acid reflux score. Vonoprazan was well tolerated and was continued for 15.5 [11.25–23.75] months in all patients. Conclusion: Vonoprazan is a potential treatment option for treating proton pump inhibitor-refractory reflux esophagitis in systemic sclerosis patients.